(untitled) (Discourse of Law and Administration, 2025)
The Act of June 9, 2022, on the Support and Resocialization of Minors does not regulate issues concerning children under 10 years of age exhibiting signs of demoralization. This article presents selected issues concerning the legal protection of such children. The author attempts to provide an up-to-date interpretation of the applicable law in this area, taking into account the literature and case law of the Supreme Court.